ESTATES OF THE MONASTERY OF ST. GEORGE GORGOS OF SKOPJE IN VELBUŽD AND VICINITY (Annual of the Faculty of Philosophy in Skopje, 2011)
The history of the Monastery of St. George Gorgos and particularly the estates it possessed is evidenced in three gift deeds: by tzar Constantine Tikh of Bulgaria from 1257/58; by the Serbian King Milutin from 1300; and by Vuk Brankovič from 13 77/78.Subject of analysis is the oldest of the preserved documents, the gift deed by tzar Constantine Tikh of Bulgaria, particularly the estates of the monastery in Velbužd and its vicinity. Researches so far have located some of these estates in Ovce Pole, Zegligovo and Velbužd. This is the village of Jovan Bogoslov, the village of Dabnica, the village- metoch of St. Vasily, the community ofPodmir, the village-metoch of St. Luka and the metoch of St. Nikola Koluški in Velbužd.The village of Jovan Bogoslov has been located in Ovce Pole, but there is also a village of Bogoslovec, near the medieval city of Velbužd, that may correspond to the donated one. Some scientist locate the village of Dabnica in the region of Prilep, but field researches have pointed to the possible location of today 's village of Rakovo, that used to be called Dabovo. The metoch of St. Vasily was supposed to be in Ovce Pole or Zegligovo, but it was probably located near the present day village of Vaksevo, in whose vicinity the katun estate of Podmir and the metoch of St. Luka (identified with the Monastery of St. Luka in the village of Granica, Kyustendil), should be looked for, the reason being that the last gift - the metoch of St. Nikola in Velbužd - is quite nearby. All these estates formed an economic unity on the way from Velbužd, through East Osogovo towards the River of Bregalnica, Ovce Pole and Skopje, along which Constantine Tikh travelled when he arrived from the Upper (Gorna) to the Lower Country (Dolna Zemja).
Keywords: ESTATES; JOVAN BOGOSLOV; DABNICA; ST VASILY; ST. LUKA; ST. NIKOLA; IMMUNITY